Perceived Social Support on the Relationship Between ADD/ADHD and Both Anxious and Depressive Symptoms Among Canadian Adults. Issue 3 (February 2023) - Connolly, Ross D.; Lamont, Allyson; Speed, David
Objective: The primary goal of the present research was to examine whether the relationships that social support demonstrates with both anxiety and depression varied between adults with and without ADD/ADHD in a Canadian sample. Method: Data were obtained from the 2012 Canadian Community Health Survey–Mental Health ( N  ≥ 16, 354). Presence of social support, diagnosis of generalized anxiety disorder (GAD), and experience of major depressive episodes (MDEs) were estimated in the self-report ADD/ADHD and non-ADD/ADHD groups. Results: Although social support was negatively associated with having GAD or experiencing an MDE, and self-report ADD/ADHD was positively associated with these outcomes. Presence of self-report ADD/ADHD did not significantly modify the relationships between social support and GAD or MDE. Conclusion: Social support may be a protective factor against symptoms of anxiety and depression in the general Canadian population, for adults with and without ADHD.